2018
DOI: 10.15244/pjoes/80866
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Machine-Learning Models for Drought Forecasting in Vietnam’s Cai River Basin

Abstract: Drought often occurs and is the costliest one of all natural disasters over the world, leading to significant societal, economic, and ecologic impacts [1-2]. Drought usually affects human lives more than any other form of natural hazards, and is widely considered to be the most complex and least understood of all the natural hazards [3-4]. Drought not only affects agricultural systems but also has a serious impact on the environment. Therefore, drought monitoring and assessment and so on, are hot topics among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…The estimated outcomes of SPI-6 and SPI-3 showed that the WANN model exhibited superior performance to other models. Liu et al [51] used the Self-Adaptive Evolutionary-Extreme Learning Machine (SADE-ELM), Online Sequential-ELM (OS-ELM), and ELM for meteorological drought prediction based on SPEI and SPI in Khanhhoa Province, Vietnam. They found that the performance of the SADE-ELM models was superior to the other models.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated outcomes of SPI-6 and SPI-3 showed that the WANN model exhibited superior performance to other models. Liu et al [51] used the Self-Adaptive Evolutionary-Extreme Learning Machine (SADE-ELM), Online Sequential-ELM (OS-ELM), and ELM for meteorological drought prediction based on SPEI and SPI in Khanhhoa Province, Vietnam. They found that the performance of the SADE-ELM models was superior to the other models.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, both methods have been proved to be computationally efficient. Various machine learning approaches have been extensively applied in the case of drought prediction (see, for example, [[28], [29], [30], [31], [32]]). The most recent work by Fung et al [33] provides a comprehensive review of the applications of statistics-based modelling as well as machine learning methods for drought forecasting over the period from 2007 to 2017.…”
Section: Methods Detailsmentioning
confidence: 99%
“…Artificial neural networks and support vector regression were used by [3] to create a model to understand the effect of drought in the New Wales region of South in Australia; The extreme learning machine (ELM) was used to identify drought situations by predicting SPI and SPEI in the Cai River Basin in Vietnam [19]; to name just those…”
Section: Word Cloud Of Drought Prediction Algorithmsmentioning
confidence: 99%